A Case of Perioral Dermatitis Successfully Treated with Abrocitinib - Teng Y; Ren M; Ding Y; Yang X; Fan Y; Tao X (Dove Medical Press, 2023)
Yan Teng,1,* Mingyang Ren,2,* Yang Ding,1 Xianhong Yang,1 Yibin Fan,1 Xiaohua Tao1 1Center for Plastic & Reconstructive Surgery, Department of Dermatology, Zhejiang Provincial People's Hospital, Affiliated People's Hospital of Hangzhou Medical College, Hangzhou, 310014, People's Republic of China; 2Graduate School of Clinical Medicine, Bengbu Medical School, Bengbu, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiaohua Tao; Yibin Fan, Center for Plastic & Reconstructive Surgery, Department of Dermatology, Zhejiang provincial people's hospital, People's Hospital of Hangzhou Medical College, Tel +86-13505811700 ; +86-18806538451, Email taoxiaohua@hmc.edu.cn; fanyibin@hmc.edu.cnAbstract: Perioral dermatitis (POD) is a chronic inflammatory skin disease that primarily affects females between the ages of 16 and 45. Conventional therapies face the challenge of limited efficacy and a high recurrence rate. In this report, we present the case of a 26-year-old male patient with POD who was successfully treated using the Janus kinase (JAK) inhibitor, abrocitinib. This treatment exhibited both good efficacy and safety. Abrocitinib, as a JAK inhibitor, holds promise as a potential therapy for cases of POD that might be resistant to conventional therapies.Keywords: JAK inhibitors, abrocitinib, perioral dermatitis